Muslim Milenial sebagai Katalisator Industri Pariwisata Halal Indonesia: Mencari Titik Temu Potensi dan Atensi - S Shofi'unnafi (JURNAL ILMIAH SYI'AR, 2020)
The existence and role of millennial Muslims to encourage the development of halal tourism in Indonesia are very vital. It aims to increase Indonesia’s Halal Tourism potential and attractiveness. Indonesia has many destinations, including natural tourism, historical (religious) tourism, as well as cultural diversity and customs from every region in Indonesia. Muslim population currently reaches 30% of the total population in the world. Indonesia has a large market potential considering the majority of the Muslim population, especially those born in the 1980-2000s or commonly referred to as millennials. Millennial Muslims are driving the development as well as the halal tourism market in Indonesia. Attention to the halal tourism industry from millennial Muslims must be increased so that Indonesia’s halal tourism industry grows and develops because non-Muslim countries are also flocking to develop that sector. Now, Muslim tourists are very enthusiastic about halal tourism, this is due to increased awareness of halal products. The increasing number of tourists who come can have an impact on people's income, tourism businesses, local and central government. Millennial Muslims could utilize technology to earth and globalize Indonesian halal tourism.